1984
DOI: 10.1902/jop.1984.55.5.299
|View full text |Cite
|
Sign up to set email alerts
|

Serum and Salivary IgG and IgA Response to Initial Preparation Therapy

Abstract: The purpose of this study was to determine and compare IgG and IgA concentration in both serum and unstimulated whole saliva obtained prior to any therapy and following initial preparation therapy (IPT) in 15 healthy adult dentulous patients, five each of periodontal disease Classes I, II and III. During the first visit before therapy, 10 ml of whole blood and 5 ml of saliva were obtained. Serum protein electrophoresis was conducted to rule out immunoglobulinopathies. Radial cell immunodiffusion endpoint techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Patients with periodontal disease are shown to have higher salivary concentrations of IgA, IgG and IgM specific to periodontal pathogens compared with healthy patients (68). Additionally, the levels of these immunoglobulins in saliva are greatly reduced after periodontal treatment (63). As a consequence, the screening of saliva, especially for IgA, has been previously discussed as a useful, noninvasive technique to identify individuals who have the potential to develop periodontal disease or those who are currently responding to a periodontopathogenic infection (51).…”
Section: Salivary Markers Of Periodontal Diseasesmentioning
confidence: 99%
“…Patients with periodontal disease are shown to have higher salivary concentrations of IgA, IgG and IgM specific to periodontal pathogens compared with healthy patients (68). Additionally, the levels of these immunoglobulins in saliva are greatly reduced after periodontal treatment (63). As a consequence, the screening of saliva, especially for IgA, has been previously discussed as a useful, noninvasive technique to identify individuals who have the potential to develop periodontal disease or those who are currently responding to a periodontopathogenic infection (51).…”
Section: Salivary Markers Of Periodontal Diseasesmentioning
confidence: 99%
“…Changes in the concentration of immunoglobulins in saliva following treatment were examined by Reiff (1984). The salivary (and serum) levels of IgG and IgA were determined in healthy adult patients, and patients with periodontal disease before and following initial periodontal therapy.…”
Section: Immunoglobulin Isotypes In Salivamentioning
confidence: 99%
“…In contrast, Bokor et al (29) reported that IgA levels in mixed unstimulated saliva were lower in subjects with more pronounced gingival inflammation. Reiff et al (227) examined serum and salivary concentrations of IgG and IgA in periodontitis patients before and after initial therapy, and found a reduction in both IgG and IgA after treatment. Basu et al (21) evaluated IgG and IgA in whole saliva from 12 periodontitis patients and found increased amounts of IgG and decreased IgA concentrations before therapy, compared to post‐treatment levels.…”
Section: Salivary and Serum Immunoglobulins As Potential Diagnostic Mmentioning
confidence: 99%